Characteristics of Pectin Extracted from Cocoa Pod Husks - Nanti - Musita (Indonesian Coffee and Cocoa Research Institute, 2021)
Cocoa plant husks is one of the source of pectin. Pectin in the food industry is used as thickener, gel agent and stabilizer. The aim of this study was to determine the characteristics of the pectin from cocoa pod husks with variation in temperature and extraction times. In this study the extraction of pectin from cocoa pod husk was carried out with hydrochloric acid solvent, with 40, 60 and 80 minutes extraction times at 65oC, 80oC, and 95oC. The results showed that the extraction temperature (65oC, 80oC, and 95oC) and extraction time (40, 60, and 80 minutes) had no significant effect on metoxyl content, galacturonat acid, equivalent weight, and pectin content, but the extraction time had a significant effect on the acetyl number and the degree of esterification. The highest yield of pectin was obtained at extraction temperature of 80oC for 60 minutes. The pectin content in cocoa pod husk is larger than the content in banana skin. The characteristics of cocoa pod husk pectin powder are brown, with moisture content 10.56-11.96%, ash content 6.82-8.97%, methoxyl content 3.51-4.86%, galacturonic acid content 41.38-88.40%, esterification degree 10.76-19.96%, acetyl number 14.55-20.90%, equivalent numbers 663.83-1549.22, pectin content 9.52-19.51 and yield 5.55- 7.70%. IR Spectrum showed that there was no difference in the functional groups between standard, commercial, and pectin extracted at different temperatures.